Facile hydrothermal preparation of titanium dioxide decorated reduced graphene oxide nanocomposite - Chang, B.Y.; Huang, N.M.; An'amt, M.N.; Marlinda, A.R.; Norazriena, Y.; Muhamad, M.R.; Harrison, I.; Lim, H.N.; Chia, C.H. (Dove Medical Press, 2012)
A simple single-stage approach, based on the hydrothermal technique, has been introduced to synthesize reduced graphene oxide/titanium dioxide nanocomposites. The titanium dioxide nanoparticles are formed at the same time as the graphene oxide is reduced to graphene. The triethanolamine used in the process has two roles. It acts as a reducing agent for the graphene oxide as well as a capping agent, allowing the formation of titanium dioxide nanoparticles with a narrow size distribution (~20 nm). Transmission electron micrographs show that the nanoparticles are uniformly distributed on the reduced graphene oxide nanosheet. Thermogravimetric analysis shows the nanocomposites have an enhanced thermal stability over the original components. The potential applications for this technology were demonstrated by the use of a reduced graphene oxide/titanium dioxide nanocomposite-modified glassy carbon electrode, which enhanced the electrochemical performance compared to a conventional glassy carbon electrode when interacting with mercury(II) ions in potassium chloride electrolyte.